The Sirt1 activator SRT3025 provides atheroprotection in Apoe−/− mice by reducing hepatic Pcsk9 secretion and enhancing Ldlr expression. (6th March 2014) - Miranda, Melroy X.; van Tits, Lambertus J.; Lohmann, Christine; Arsiwala, Tasneem; Winnik, Stephan; Tailleux, Anne; Stein, Sokrates; Gomes, Ana P.; Suri, Vipin; Ellis, James L.; Lutz, Thomas A.; Hottiger, Michael O.; et al.
Abstract: Aims: The deacetylase sirtuin 1 (Sirt1) exerts beneficial effects on lipid metabolism, but its roles in plasma LDL-cholesterol regulation and atherosclerosis are controversial. Thus, we applied the pharmacological Sirt1 activator SRT3025 in a mouse model of atherosclerosis and in hepatocyte culture. Methods and results: Apolipoprotein E- deficient ( Apoe −/− ) mice were fed a high-cholesterol diet (1.25% w/w) supplemented with SRT3025 (3.18 g kg −1 diet) for 12 weeks. In vitro, the drug activated wild-type Sirt1 protein, but not the activation-resistant Sirt1 mutant; in vivo, it increased deacetylation of hepatic p65 and skeletal muscle Foxo1. SRT3025 treatment decreased plasma levels of LDL-cholesterol and total cholesterol and reduced atherosclerosis. Drug treatment did not change mRNA expression of hepatic LDL receptor (Ldlr) and proprotein convertase subtilisin/kexin type 9 (Pcsk9), but increased their protein expression indicating post-translational effects. Consistent with hepatocyte Ldlr and Pcsk9 accumulation, we found reduced plasma levels of Pcsk9 after pharmacological Sirt1 activation. In vitro administration of SRT3025 to cultured AML12 hepatocytes attenuated Pcsk9 secretion and its binding to Ldlr, thereby reducing Pcsk9-mediated Ldlr degradation and increasing Ldlr expression and LDL uptake. Co-administration of exogenous Pcsk9 with SRT3025 blunted these effects. Sirt1 activation with SRT3025 in Ldlr −/− mice reduced neither plasma Pcsk9, nor LDL-cholesterol levels, nor atherosclerosis. Conclusion: We identify reduction in Pcsk9 secretion as a novel effect of Sirt1 activity and uncover Ldlr as a prerequisite for Sirt1-mediated atheroprotection in mice. Pharmacological activation of Sirt1 appears promising to be tested in patients for its effects on plasma Pcsk9, LDL-cholesterol, and atherosclerosis.